The Role of Teachers in Developing the Morals of Children Aged 5-6 Years in Private Kindergarten Petro T.A 2022/2023 - Violita Purba; Sariana Marbun (Indonesian Journal of Advanced Research, 2023)
This study aims to determine the moral development achievements of children aged 5-6 years and the role of teachers in developing the morale of children aged 5-6 years. This research is a qualitative descriptive study. Data was collected through observation, interviews and documentation. The results showed that 1) The achievement of the moral development of children aged 5-6 years, the majority of children's moral development which had developed very well consisted of 9 children and those whose moral development had developed quite well consisted of 4 children. 2) the role of the teacher in developing the morale of children aged 5-6 for the first time, the role of the teacher as a model in developing the morale of the teacher applies it by applying daily habits by greeting each other, saying hello, praying before and after carrying out teaching and learning activities, giving advice by a fun way, and invites children to socialize with the environment.